I am my own woman : the outlaw life of Charlotte von Mahlsdorf, Berlin's most distinguished transvestite. - Mahlsdorf, Charlotte von (Pittsburgh : Cleis Press Inc., 1995)
Fonds Suzan Daniel (FSD)
Engels
Monografie